Rap e repente: do tecer das rimas ao canto falado - Tolentino, Andréia Ramalheiro (2009)
The present research runs upon the importance of oral tradition in contemporary age, an age characterized by the loss of traditional references.It examines "rap" and "repente" as oral poetics that represent popular culture and tell the globalization effects, consequence of the current economic system. The research aimed at identifying the similarities between these two popular musical manifestations, ressignifying the action of cultural agents responsible for the continuance of such tradition, characterized by spoken singing. Under a cultural perspective, it created a dialogue with the interviewed subjects, in order to clarify both their world vision and the way they organize their social practices. By doing so, it was possible to see the elements which allow the comprehension of artistic and social representations of such groups.